The utility of mathematics support centre feedback to lecturers of large first-year university mathematics courses. Issue 10 (26th November 2021) - Cronin, Anthony; Meehan, Maria
ABSTRACT: This paper examines the various ways in which university lecturers of large first-year university mathematics courses receive and use feedback on their students' learning with particular emphasis on feedback collected at a mathematics support centre in an Irish university. Drawing on findings from interviews conducted with 13 lecturers at three intervals in a teaching semester, we present ten ways, identified by lecturers, in which they receive feedback on their students' learning. We examine the utility of mathematics support centre feedback to lecturers wishing to monitor their students' progress as the module unfolds. This electronic feedback, supplied by the attending mathematics support tutor(s), gives a brief summary of each student's query to the centre. We describe lecturers' reports of where this feedback sits in the general context of other feedback sources from large classes and how it can be useful. Lecturers' responses were analysed using thematic analysis, and three key aspects of feedback emanating from a mathematics support centre were identified: its uniqueness and value; its detail and specificity; and, its impact on practice. We found that lecturers perceive this form of feedback to be one of the most valuable available to them in terms of formatively assessing their students' learning.